2016
DOI: 10.1016/j.bmcl.2016.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Initial investigation of three selective and potent small molecule oxytocin receptor PET ligands in New World monkeys

Abstract: The neuropeptide oxytocin is part of a neuroendocrine system that has physiological effects ranging from ensuring uterine myometrial contractions at parturition and post-partum mammary gland milk ejection to the modulation of neural control of social relationships. This initial study was performed to investigate the potential use of positron emission tomography (PET) for localizing oxytocin receptors in two New World primates. Three biomarkers for PET (1 – 3) that are known to have high affinity and selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…[ 11 C]GSK711320 did not appear to significantly enter the brain; the higher activity uptake was seen in the pituitary gland and in the choroid plexus with no brain region demonstrating a high accumulation and retention of radioactivity. Similar high uptake in these regions and low CNS uptake has been observed with previously reported oxytocin radiotracers, 18,20,21 and [ 3 H] oxytocin has also been shown to bind to the neural lobe of the pituitary; 29 this binding was however demonstrated to be associated to binding to neurophysins.…”
Section: Pet Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…[ 11 C]GSK711320 did not appear to significantly enter the brain; the higher activity uptake was seen in the pituitary gland and in the choroid plexus with no brain region demonstrating a high accumulation and retention of radioactivity. Similar high uptake in these regions and low CNS uptake has been observed with previously reported oxytocin radiotracers, 18,20,21 and [ 3 H] oxytocin has also been shown to bind to the neural lobe of the pituitary; 29 this binding was however demonstrated to be associated to binding to neurophysins.…”
Section: Pet Studiessupporting
confidence: 84%
“…14,15 For in vivo SPECT imaging, Gallium-67 labelled OT has been reported. 16 Recently, several candidate molecules were evaluated for in vivo imaging of the central OTR; [17][18][19][20][21][22] however, despite some encouraging in vitro results, PET imaging studies showed either no significant brain uptake or a limited CNS distribution that did not correspond to the expected OTR distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This report confirms the variance in brain penetration of [ 18 F]ALS-I-41 between animal models as, previously reported, no significant brain penetration of [ 18 F]ALS-I-41 was detected in titi monkey models. [53] However, the data from the various rat scans does lead to the hypothesis that if a 30 minute continuous IV infusion of [ 18 F]ALS-I-41 is performed with a macaque model then an image with improved resolution may be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The neurochemicals which are responsible for the higher rCGM in some regions remain to be confirmed. Chemically specific PET ligands are available for some of these (such as dopamine D1 and D2 receptors); however, there is still no OT receptor PET ligand (Smith et al, 2016), and no easily available V1a receptor PET ligand. Finally, the neural basis of other aspects of the pair-bond, such as separation distress and mate-guarding (or “jealousy”), also remain to be considered.…”
Section: Discussionmentioning
confidence: 99%